BREEDER SEED POTATO PRODUCTION THROUGH CONVENTIONAL AND HI-TECH SYSTEMS – A COMPARATIVE STUDY IN HIGH HILLS OF NORTH WESTERN INDIA - Sharma, Ashwani K; Kumar, Vinod; Pandey, K K (Potato Journal, 2016)
The conventional system of seed potato production involving clonal multiplications is being replaced with micro-propagation techniques (hi-tech system) on account of numerous advantages possessed by the later. High hills of northwestern India are ideally suited for the production of breeder seed potatoes. Thus, nucleus and breeder seed potatoes for the hilly regions of India are produced at Central Potato Research Station, Kufri (Fagu), Shimla hills at an average altitude of 2700m above mean sea level. Since 2008, seed potato production through micro-propagation techniques has also been introduced at the station. To know the comparative efficiency of both the systems of seed potato production, a study was conducted during 2011 and 2012 involving the important cultivars of the region. The study revealed that both the systems of seed potato production proved equally good with regard to plant growth vigour, disease freedom as well as for the tuber number of tubers and productivity. It can be attributed to the slow rate of degeneration of seed stocks in either of the production systems due to low vector pressure prevailing in high hills of north-western India. Among the cultivars, Kufri Himalini recorded the maximum yield with minimum number of tubers per ha while Kufri Girdhari had the maximum number of tubers with mini-yields.